Psoas Abscess Due to Aeromonas hydrophila: Case Report - Hicran KARAOĞLAN (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2004)
Forty-one years old male patient who was operated on with the diagnosis of acute necrotizing pancreatitis admitted with probable intraabdominal infection. We determined psoas abscess which fistulized to the skin of abdominal wall by radiological examinations. As Aeromonas hydrophila was isolated from the pus, the patient was evaluated for the risk factors. Intraabdominal infection was treated by imipenem during three weeks without any surgical intervention. The patient remained symptomless during three months follow up. The case was presented because of the unusual psoas abscess which was caused by A. hydrophila.